ANALYSIS OF THE INFLUENCE OF BRAND EXPERIENCE, APPLICATION EASE OF USE, AND PERCEIVED QUALITY ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY IN THE PIJAR SEKOLAH APPLICATION (A CASE STUDY OF PUBLIC JUNIOR HIGH SCHOOLS, VOCATIONAL HIGH SCHOOLS, AND SENIOR HIGH SCHOOLS IN WEST BANDUNG REGENCY) - Fina Septiani; Putu Nina Madiawati; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2025)
This study analyzes the influence of brand experience, application ease of use, and perceived quality on customer satisfaction and its impact on customer loyalty in the PIJAR Sekolah application. The research focuses on users from public junior high schools, vocational high schools, and senior high schools in West Bandung Regency. A quantitative method was employed using a survey distributed to students and educators. The data were analyzed using Structural Equation Modeling (SEM). Results show that brand experience, ease of use, and perceived quality significantly influence customer satisfaction. Furthermore, customer satisfaction plays a critical role in driving customer loyalty. The study emphasizes the importance of enhancing user interaction, simplifying application navigation, and ensuring content quality to boost satisfaction and long-term usage. These findings offer insights for educational technology developers to improve digital learning platforms and foster user loyalty through an optimized experience.